2015
DOI: 10.1016/j.ajo.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

En Face Optical Coherence Tomography of Foveal Microstructure in Full-Thickness Macular Hole: A Model to Study Perifoveal Müller Cells

Abstract: INTRODUCTIONEn-face optical coherence tomography (OCT) is an emerging imaging modality that facilitates the assessment of retinal structures transversely.1,2 Available since 2006 on certain OCT devices, the first retinal transverse scans were difficult to analyze interpret as only plane sections of the concave retina were available. 3 More recently, Spectral-Domain OCT technology with advanced alignment algorithm have adjusted sections to a reference curve, which has allowed layer-by-layer retinal imaging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 31 publications
6
53
2
3
Order By: Relevance
“…We measured the mean values of the area on the perpendicular images with OCT radial scans and confirmed that the horizontal and vertical images had the same cystoid cavities. However, some studies have evaluated the cystic areas in the en face OCT images, and similar measurements in our patients would probably lead to a more precise assessment of the cystic areas 29,31 . Third, the follow-up period was relatively short.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We measured the mean values of the area on the perpendicular images with OCT radial scans and confirmed that the horizontal and vertical images had the same cystoid cavities. However, some studies have evaluated the cystic areas in the en face OCT images, and similar measurements in our patients would probably lead to a more precise assessment of the cystic areas 29,31 . Third, the follow-up period was relatively short.…”
Section: Discussionmentioning
confidence: 75%
“…Previous study combining the immunohistochemistry with en face OCT images demonstrated the features of the cystoid cavities 29 www.nature.com/scientificreports www.nature.com/scientificreports/ Gass classified MHs by the extent of the vitreomacular adhesion: Stage 2, partial detachment of the posterior hyaloid; Stage 3, total detachment of the posterior hyaloid but still attached to the optic disc; and Stage 4, complete detachment of the posterior vitreous 1 . In our results, the Stage 3 eyes had significantly larger cystoid areas and higher ELM height than Stage 2 or Stage 4 MH eyes.…”
Section: Discussionmentioning
confidence: 99%
“…; Matet et al. ). At the ELM, Müller cells contain contractile rings of filamentous actin which enclose the photoreceptors; these rings are associated with the junctions between Müller and photoreceptor cells and form a structural meshwork in which photoreceptors are embedded (Del et al.…”
Section: Discussionmentioning
confidence: 97%
“…A steeper slope of the OLM can be also produced by a vertical contraction of the stalk of the Müller cell cone in the center of the foveola (Figure c) (Bringmann et al, ). The Müller cell‐mediated displacement of foveal photoreceptors is supported by tight‐like junctions between Müller and photoreceptor cells in the outer retina and at the OLM (Matet et al, ; Omri et al, ). This mechanism may be one basis of the remarkable capacity of photoreceptors to realign themselves towards the pupil after retinal detachment or pupil displacement (Enoch, van Loo Jr., & Okun, ).…”
Section: Müller Cells Of the Foveamentioning
confidence: 99%
“…The latter was suggested to be mediated by a radial contraction of the receptor segments and a horizontal contraction of Müller cell structures which surround the photoreceptor cells at the OLM (Bringmann et al, ; Provis, Dubis, Maddess, & Carroll, ). Photoreceptor and Müller cells are tightly glued together in the HFL and ONL, and at the OLM (Matet et al, ; Omri et al, ). At the OLM, Müller cells contain contractile rings of filamentous actin which enclose the photoreceptors; the rings are connected with the junctions between Müller and photoreceptor cells and form a structural meshwork in which photoreceptors are embedded (Del Priore, Lewis, Tan, Carley, & Webb, ).…”
Section: Development Of the Foveamentioning
confidence: 99%